2008
DOI: 10.1111/j.1540-8167.2008.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Primary Prevention Implantable Cardioverter‐Defibrillators in the Setting of Chronic Kidney Disease: A Decision Model Analysis

Abstract: Our model shows that benefit from primary prevention ICD implantation is determined by the patient's age and stage of kidney disease. While there is limited impact with lower stages of CKD, careful consideration of ICD implantation is suggested for older patients with more advanced stages of kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 34 publications
2
57
0
1
Order By: Relevance
“…The utility of implantable cardioverter‐defibrillators (ICDs) has not been well studied in patients with CKD and ESRD, who historically have been excluded from clinical trials investigating ICD use in patients with CHF. Patients who meet the criteria for ICD placement for primary prevention often are not offered these devices because of lower life expectancy, higher rates of device complications, and other comorbidities 86. Patients with advanced CKD and ESRD tend to have higher rates of acute and chronic complications from device placement and higher mortality unrelated to cardiac arrhythmias 86.…”
Section: Chf In Patients With Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of implantable cardioverter‐defibrillators (ICDs) has not been well studied in patients with CKD and ESRD, who historically have been excluded from clinical trials investigating ICD use in patients with CHF. Patients who meet the criteria for ICD placement for primary prevention often are not offered these devices because of lower life expectancy, higher rates of device complications, and other comorbidities 86. Patients with advanced CKD and ESRD tend to have higher rates of acute and chronic complications from device placement and higher mortality unrelated to cardiac arrhythmias 86.…”
Section: Chf In Patients With Esrdmentioning
confidence: 99%
“…Patients who meet the criteria for ICD placement for primary prevention often are not offered these devices because of lower life expectancy, higher rates of device complications, and other comorbidities 86. Patients with advanced CKD and ESRD tend to have higher rates of acute and chronic complications from device placement and higher mortality unrelated to cardiac arrhythmias 86. A study of a cohort of >9500 patients on chronic dialysis implanted with ICDs revealed that 11% of patients died of an infection at 1.4 years of follow‐up, with most infections occurring 1 year after device implantation 87.…”
Section: Chf In Patients With Esrdmentioning
confidence: 99%
“…16) Nevertheless, age and sex can also affect survival in patients with ICD implantation. 50,51) Conclusions: This is the first meta-analysis reporting that ICD implantation reduces all-cause mortality in stage 3 CKD patients. However, the survival benefit of ICD implantation in CKD patients with stage 4 or 5 is not supported by these data.…”
Section: )mentioning
confidence: 99%
“…ICD therapy was only associated with a survival benefit in patients with eGFR ≥ 35 ml/min/1.73m 2 but not in patients with eGFR <35ml/min/1.73m 2 . Using a decision analysis model of primary prevention ICD implantation, Amin et al showed that ICD implantation in patients with CKD stage V was only favoured in those aged <65 years (Amin et al, 2008). The benefit of ICD therapy in dialysis patients is questionable.…”
Section: Role Of Implantable Cardioverter Defibrillator For Primary Pmentioning
confidence: 99%